Outcome of Operative Versus Conservative Management of Humeral Shaft Fractures: A Longitudinal Study - Sartaj Lakhani, Ghias Uddin Jan, Mehtabullah, Niaz Hussain Keerio, Imtiaz Ahmed Tago, Zulfiqar Ali Zaur, Syed Shahid Noor (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the outcome of operative versus conservative management of humeral shaft fractures. Study design: A longitudinal study Place and Duration: This study was conducted at Civil Hospital Mithi District Tharparkar Pakistan from July 2020 to July 2021. Methodology: The study included 30 patients having humeral shaft fractures who were divided into two groups. One group was managed conservatively whereas the other was managed surgically. The patients were followed up for 1 year and the clinical and radiological examination was performed to assess the complications and clinical outcomes. Results: Most of the patients who have humeral fractures were because of roadside accidents. No significant differences were present in the time of union between both groups, similarly, elbow ROM at the fracture union was also not significantly different. However, malunion was more frequently observed in the conservatively managed group which was 12.7% as compared to the operative group which was 1.3%. Conclusion: No significant difference was observed in reference to the timing of union between the two groups. All humeral fractures need an assessment before opting the conservative or operative management depending upon patient expectations and characteristics of fractures.